RELASI HAK DAN KEWAJIBAN SUAMI ISTRI UPAYA MEWUJUDKAN KETAHANAN KELUARGA PADA MASA PANDEMI (Di Desa Bondolharjo Kecamatan Punggelan Kabupaten Banjarnegara) - M. SYAIFUL ABIDIN (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2022)
The relationship of husband and wife rights and obligations is a mutually supportive relationship because of the love to continue their domestic life. One of the factors that affect family resilience is related to economic income. In normal times, resilience goes on as usual, but during a pandemic, the income side of the economy undergoes changes that can cause maintaining a family to shift. Families of casual daily workers in Bondolharjo village, Punggelan sub-district, Banjarnegara district during the pandemic are trying to focus on building their family's resilience during the pandemic. With the aim that his family is resilient and able to fight in facing the challenges that occur today. The analysis of the rights and obligations of husband and wife for families of casual daily workers in Bondolharjo village in an effort to realize family resilience during the pandemic has led to an equal direction, sharing work and one party does not govern or adapt to his desires and needs to win on his own. Married couples agree to share work and daily activities, take responsibility for their respective jobs and obligations, and fulfill responsibilities together.